Indigenous Knowledge : The East Africa-South Asia Learning Exchange - An Example of South-South Cooperation - World Bank (World Bank, Washington, DC, 2012)
Inspired by the success of the pilot study tour, the Africa Region embarked on an initiative to build cross-regional partnership between East Africa and South Asia seeking to integrate indigenous knowledge and practices into Bank supported operations. The aim was to leverage the experience of IK good practices from South Asia into Bank supported projects in East Africa. This would also help foster new partnerships for South-South dialogue, cooperation and technical assistance. The focus was on indigenous knowledge as it is a key element of the social capital of the poor, assisting them in their struggle to improve their livelihoods. For example, farmers have used organic fertilizers to increase soil fertility in parts of Asia and Africa for centuries; similarly, local healers have used medicinal plants in India and Tanzania to treat common human, and animal diseases. Many local organizations, institutions, and communities have a wealth of knowledge of IK practices. However, these practices are not disseminated effectively because community-based organizations lack the capacity to capture, document, validate and share them.